Collection protocols for the recovery of biological samples. (December 2015) - Aloraer, D.; Hassan, N.H.; Albarzinji, B.; Goodwin, W.
Abstract: The main focus in forensic genetics for two decades has been to improve the extraction of DNA from a wide variety of evidence and to make the profiling technology more sensitive and robust. In contrast, the recovery methods for biological material have seen little development. This study aims to improve the efficacy of the collection and storage processes, from crime scene to receipt at the laboratory. This study compared the use of ultrapure water as a wetting agent when collecting biological evidence using swabs with a detergent-based buffer. The results show that the stability post-collection greatly improved by using a newly developed buffer. When ultrapure water is used, DNA degradation was seen after 6 h at room temperature. However, the detergent-based buffer stabilized DNA for up to 48 h, even when the temperature was increased to 50 °C. The impact of these findings may be limited where crime scene evidence can be refrigerated until it reaches the laboratory. However, there are many situations/contexts where sample refrigeration is not possible and there is scope to improve the preservation of the genetic forensic evidence before it reaches the laboratory.